The quality assessment of starch based noodles enriched with Noui Khuea brown rice starch, physicochemical characteristics and functional properties - Kaewnak, Nounhong; Chumsri, Paramee (Creative Science, 2025)
This study aimed to develop starch-based noodles enriched with Noui Khuea (NK) brown rice starch by substituting rice starch at six different levels (0%, 20%, 40%, 60%, 80%, and 100%). The research was designed to investigate how varying proportions of NK brown rice starch influence the physicochemical, functional, and quality characteristics of the noodles. Specifically, the study evaluated parameters such as color, moisture, and water activity (aw) and viscosity and bulk density. By systematically substituting rice starch with NK brown rice starch, the study sought to determine the optimal substitution level that balances desirable noodle quality with enhanced nutritional value. The physicochemical characteristics and functional properties of the noodle samples were systematically evaluated. Substitution with NK brown rice starch resulted in significant improvements in nutritional and functional properties. At 100% substitution, the noodles exhibited the highest DPPH radical scavenging activity (35.7%), indicating superior antioxidant potential compared to the control (11.18%). Water absorption capacity and swelling index increased from 1.30 to 1.80 g g-1 and 5.06 to 6.50 g g-1, respectively, while peak viscosity rose from 225.60 cP in the control to 307.93 cP, reflecting better gelatinization behavior and stability under heat. This research introduces an innovative approach to noodle development by incorporating Noui Khuea brown rice—a local, underutilized rice variety from Southern Thailand—into functional food applications. The study demonstrates how local agricultural resources can be creatively transformed into high-value products with enhanced health benefits, aligning with the principles of Creative Science and sustainable development. GRAPHICAL ABSTRACT HIGHLIGHTS Noui Khuea brown rice starch was used to enrich starch-based noodles formulation. Physicochemical and functional properties of the enriched noodles were evaluated. Noodles with Noui Khuea starch showed improved viscosity and water/oil absorption.